Grandpa, me & poetry - Morgan, Sally, 1951 January 18-; Smith, Craig, 1955- (Gosford, NSW : Omnibus Books, an imprint of Scholastic Australia, 2018)
Melly likes poems that rhyme with words like frog, bog, doggedy-dog. And when the school holds a poetry competition, Melly has her eye on the prize, with a little bit of inspiration from Grandpa.
Keywords: Grandparent and child -- Juvenile fiction; Children, Aboriginal Australian -- Juvenile fiction; Poetry -- Juvenile fiction; Australian